2018
DOI: 10.4103/0972-9062.234621
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Leishmania species using N-acetylglucosamine-1-phosphate transferase gene in a zoonotic cutaneous leishmaniasis focus of Iran

Abstract: The findings of this study demonstrated that the main causative agent of CL in Ilam Province is L. major, and there is no considerable heterogeneity among the L. major isolates. Moreover, nagt gene proved to be an efficient marker for differentiating Leishmania species. Further studies with more samples need to be carried out to achieve a more comprehensive result on the genetic variation of L. major isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Species discrimination is important, because of differences among the Leishmania species in levels of virulence and responses to the various chemical drugs (8,9). As a result, distinguishing Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%
“…Species discrimination is important, because of differences among the Leishmania species in levels of virulence and responses to the various chemical drugs (8,9). As a result, distinguishing Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%
“…The highest intra-species divergence was seen in L. major Sabzevar. However, Hajjaran et al ( 17 ) no intra-specific differences were observed in Leishmania isolates in Ilam province using the nagt gene. This could be due to the less relationship of the inhabitants of Sabzevar and the presence of an interspecies divergence of nagt gene.…”
Section: Discussionmentioning
confidence: 95%
“…Identification of Leishmania species usually relies on DNA amplification and sequence analysis. Conventional molecular methods using different molecular targets have been used to detect Leishmania spices and find genetic diversity in cases from Iranian leishmaniasis foci ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The N-acetylglucosamine-1-phosphate transferase (Nagt) is considered as a single-copy housekeeping gene encoding the endoplasmic reticulum (ER) transmembrane protein, which is highly conserved among Leishmania species. The length of this gene is 1401 base pairs, and it could be known as an ideal target to characterize Leishmania species [27,28]. The genetic clustering has considered as an important issue in many fields of study such as ecology, medicine, and epidemiology [23,[28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The length of this gene is 1401 base pairs, and it could be known as an ideal target to characterize Leishmania species [27,28]. The genetic clustering has considered as an important issue in many fields of study such as ecology, medicine, and epidemiology [23,[28][29][30][31][32][33][34][35][36]. However, there are limited available data on the frequency and distribution of various species of Leishmania in Iran.…”
Section: Introductionmentioning
confidence: 99%